Moving on Up: Division I Athletic Directors’ Career Progression and Involvement - Robin Hardin; Coyte G. Cooper; Landon T. Huffman (Journal of Applied Sports Management, 2013)
Collegiate athletic directors (ADs) are the chief executive officers within the athletic department of the colleges and universities they serve. While they are certainly high-profile, influential professionals, there are a limited number of research studies that focus in-depth on the career experiences of these athletic administrators. The purpose of this research was to examine the career experiences of athletic directors. The results showed a shift in the need for athletic directors to understand business and development and obtain a graduate degree. More than 80% held a master’s degree with previous areas of employment in development and marketing. Such skills were also shown in involvement as ADs indicated they were heavily involved in budget oversight and development. Other areas of involvement included policy-making and community relations. There was limited involvement in actual sport operations.
Keywords: Athletic directors; college athletics; career experiences; responsibilities; NCAA